Kriging Method Of Study Of The Groundwater Quality Used For Irrigation - Case Of Wadi Djendjen Plain (north-east Algeria) - Boufekane, A.; Saighi, O. (University of Eloued جامعة الوادي, 2016)
The groundwater of wadi Djendjen plain (Jijel, North-East Algeria) have always been used as drinking water supply in the cities and the irrigation of agricultural lands. This confers this aquifer, which has already been the subject of numerous hydrogeological studies, a particular interest in terms of qualitative and quantitative monitoring. Its exploitation is today encountering excessive salinity problems, evidenced by measurements of the electrical conductivity of the water and the alkalinisation of soils. This degradation of the environment results, among others, from ion exchange which involves cations (sodium, calcium and magnesium), water / clay interaction as reflected by the sodium absorption ratio (SAR). Analyses on samples of groundwater destined for irrigation and the application of a geostatistical approach have enabled to map the most affected zones by this phenomenon.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 02
Keywords: Groundwater; quality; Irrigation; Geostatistical analysis; Kriging.